Designing Scientific Writing Syllabus for Undergraduate Student - Ni’amah, Afi; Kristanti, Ika Lusi (Institut Agama Islam Negeri Kudus, 2020)
Teaching English needs appropriate syllabus in each course. Writing course is one of courses that has great influence in composing article. Enabling undergraduate students to write in English needs well-organized and appropriate plan that students have no problem in writing. Han (2013) highlights the importance of thesis writing on both teachers and students by proving the use of Slade’s step to solve students’ problem in writing each part of thesis. The purpose of the study is to design topics in Scientific Writing syllabus for undergraduate students in composing research article. This study implemented DDR with qualitative method. In designing syllabus, ADDIE model of Dick and Carey (2015) is used. The result indicates there are five significant topics in designing Scientific Writing syllabus. Those topics are designed by concerning undergraduate students’ problem that ease them in research article writing.